2020
DOI: 10.1088/1751-8121/abcf57
|View full text |Cite
|
Sign up to set email alerts
|

BLUES iteration applied to nonlinear ordinary differential equations for wave propagation and heat transfer

Abstract: The iteration sequence based on the BLUES (Beyond Linear Use of Equation Superposition) function method for calculating analytic approximants to solutions of nonlinear ordinary differential equations with sources is elaborated upon. Diverse problems in physics are studied and approximate analytic solutions are found. We first treat a damped driven nonlinear oscillator and show that the method can correctly reproduce oscillatory behaviour. Next, a fractional differential equation describing heat transfer in a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…For nonlinear ODEs with source or sink terms, the BLUES function method has been studied intensively [7,8,9,11] and anticipated in [12]. For PDEs with a first-order time derivative, the role of the source was taken up by the initial condition multiplied by a Dirac point source located at t = 0 [10].…”
Section: Blues Function Methods For Nth-order Time Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…For nonlinear ODEs with source or sink terms, the BLUES function method has been studied intensively [7,8,9,11] and anticipated in [12]. For PDEs with a first-order time derivative, the role of the source was taken up by the initial condition multiplied by a Dirac point source located at t = 0 [10].…”
Section: Blues Function Methods For Nth-order Time Derivativesmentioning
confidence: 99%
“…Recently, it has been demonstrated that the theory of Green functions can be usefully extended to inhomogeneous nonlinear ordinary differential equations (ODEs), effectively using superposition beyond the linear domain [7,8,9]. Consequently, we probed the usefulness of the BLUES function method in the arena of nonlinear partial differential equations (PDEs) with a first-order time derivative where the initial condition plays the role of the inhomogeneous source by multiplication with a Dirac delta point source located at time t = 0 [10].…”
Section: Introductionmentioning
confidence: 99%
“…The zeroth approximant (11) is the convolution of the matrix Green function with the source vector ψ(t), i.e.,…”
Section: Blues Function Methods For the Sirs Modelmentioning
confidence: 99%
“…Here we extend the BLUES iteration originally developed for ordinary DEs [9][10][11] and partial DEs [12] to a system of coupled ordinary DEs. The role of the inhomogeneous source (or sink) term in the context of the ordinary DE will now be taken over by a vector of sources (or sinks).…”
Section: Tionsmentioning
confidence: 99%
See 1 more Smart Citation